2010
DOI: 10.1007/s00428-010-0913-9
|View full text |Cite
|
Sign up to set email alerts
|

Detection and clinical significance of bone marrow involvement in patients with rhabdomyosarcoma

Abstract: Childhood rhabdomyosarcoma (RMS) has two major histological subtypes: alveolar (aRMS) and embryonal. The aim of the study was to monitor minimal disseminated disease (MDD) using real-time quantitative reverse-transcription PCR (RQ-RT-PCR) of the PAX3-FKHR, PAX7-FKHR fusion genes and myoD1 gene. We prepared an assay using RQ-RT-PCR for a quantitative assessment of MDD in aRMS by using hydrolysis probe for quantification of PAX3-FKHR, PAX7-FKHR and myoD1 genes and beta-2-microglobulin housekeeping gene. Primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Detection of the fusion transcripts BCOR-CCNB3 in the bone marrow suggests that patients with positive findings are at high risk of the tumor progression. The frequency of BM RT-PCR positive cases in clinically non-metastatic patients was similar to that described in patients with Ewing sarcomas [16,17,18], in rhabdomyosarcomas [19,20,21], or in neuroblastoma [22].…”
Section: Discussionsupporting
confidence: 70%
“…Detection of the fusion transcripts BCOR-CCNB3 in the bone marrow suggests that patients with positive findings are at high risk of the tumor progression. The frequency of BM RT-PCR positive cases in clinically non-metastatic patients was similar to that described in patients with Ewing sarcomas [16,17,18], in rhabdomyosarcomas [19,20,21], or in neuroblastoma [22].…”
Section: Discussionsupporting
confidence: 70%
“…Studies have shown that alveolar RMS tends to involve BM more frequently than ERMS. BM metastases at diagnosis signifies worse prognosis than with metastases to other organs 5 6. Inclusion of BM trephine biopsy as a routine part of the investigation of patients with features of BM failure is essential and clinicians should be aware of the fact that ARMS frequently masquerade as haematological malignancies 7.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary DNA was prepared from 1 µl of RNA in 20 µl of reaction volume. The protocol was described by Krsková et al [21].…”
Section: Methodsmentioning
confidence: 99%